KESALAHAN TATA BAHASA YANG SERING DIJUMPAI DALAM KELAS WRITING - Aninda Aji Siwi (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2018)
Writing is one of the skills that English Literature students must master in their academic life. Good or bad of the students’ writing will be seen from their grammar. It can be imagined that if their writing is not written in good grammar, people will get confused in understanding the content of their writing. This article shows the readers about the errors that often be seen in the students’ writing. The findings explain that there are seven types of errors, for instance verb/tenses, subject verb agreement, lack of subject verb in a sentence, parallel structure, run-on sentences, gerund, and noun. The readers will learn from those errors and it is hoped that this article will give much attention to the learners not only for their writing, but also their speaking in English